Highlighting a Digital Platform to Assess Young People Needs: Reaching and Engaging Adolescents and Young Adults for Care Continuum in Health Project (REACH) - Peter Memiah; Monica Lathan-Dye; Yvonne Opanga; Samuel Muhula; Nyawira Gitahi-Kamau; Anne Kamau; Lillian Otiso (MDPI AG, 2022)
Young people (YP), defined as individuals aged between 10 and 24 years, are a vulnerable population. Leveraging digital platforms to reach YP is essential in identifying protective and risk behaviors among this population. The objectives of this study were to (1) examine the user-inclusive development process of a theory-based digital platform to reach YP, (2) describe aspects of the digital application prototype, and (3) provide preliminary findings from the utilization of the app. We present the five-step design process for building the app. The app, known as the REACH-AYA survey, consisted of 98 closed-ended questions with built-in skip-logic algorithms and took approximately 7 min to complete. The survey questions centered on behavioral, lifestyle, and psychosocial factors, which were adopted from different validated instruments, thereby addressing 10 different domains. During the pilot phase, participants utilized the app, critiqued its features, and provided iterative feedback. We used respondent-driven sampling to recruit participants in Nairobi, Kenya, the leading county in high-speed data connectivity. Once recruited, each participant completed the survey and later sent it to their peers until the desired sample size was achieved. The REACH-AYA app prototype was guided and developed by the design thinking approach with an initial pilot sample of 33 YP for pre-testing. The end-user pre-testing assessed for functionality, time, and adaptability. The app was then launched initially through social media, reaching 1101 YP, with approximately eighty percent (n = 887) having completed the survey by the close of the study. The majority of the participants were male (59%), and approximately (69%) of the participants were aged between 15 and 24 years. This is one of the few studies that demonstrate user-centric methodologies of app development and real-life application in identifying protective and risk factors for the wellbeing of YP. Methodologies and lessons learned from this research may benefit other disciplines using digital technology to reach YP or other difficult-to-reach populations.